Stable Water Isotope Assessment of Tundra Wetland Hydrology as a Potential Source of Arctic Riverine Dissolved Organic Carbon in the Indigirka River Lowland, Northeastern Siberia - Takano, Shinya; Yamashita, Youhei; Tei, Shunsuke; Liang, Maochang; Shingubara, Ryo; Morozumi, Tomoki; Maximov, Trofim C.; Sugimoto, Atsuko (Frontiers in Earth Science, 2021)
Arctic tundra wetlands may be an important source of dissolved organic carbon (DOC) in Arctic rivers and the Arctic Ocean under global warming. We investigated stable water isotopes and DOC concentration in wetlands, tributaries, and the mainstream at the lower reaches of the Indigirka River in northeastern Siberia during the summers of 2010–2014 to assess the complex hydrology and role of wetlands as sources of riverine DOC. The wetlands had higher values of δ18O and DOC concentration than the tributaries and mainstream of the Indigirka River. A relationship between the two parameters was observed in the wetlands, tributaries, and mainstream, suggesting the wetlands can be a source of DOC for the mainstream through the tributaries. The combined temporal variations in riverine δ18O and DOC concentration indicate the mainstream water flowed into the tributaries during relatively high river-level periods in summer, whereas high DOC water in the downstream wetlands could be discharged to the mainstream through the tributaries during the low river-level periods. A minor fraction (7–13%) of riverine and wetland DOC was degraded during 40 days of dark incubation. Overall, the downstream wetlands potentially provide relatively less biodegradable DOC to the Arctic river and costal ecosystem during the low river-level periods—from late summer to autumn.